(untitled) (International Journal of Business, Economics and Management, 2017)
Considering the case of China the present study necessitates to highlight the environment quality of the country in the wake of increasing trends of FDI. This study attempts to present both the empirical as well as technical approach to explain the consequences of FDI and factors in relation to environments. In this study critical review of the empirical studies on the subject has been presented and following that cross years and province study among Chinese provinces was done by using time series and panel data regression to define the significance of environment quality in terms of sulphur dioxide emission and water pollutants emission due to increased FDI. Time period considered was 2003-2014. Lastly, the impact of foreign direct investment on the environmental degradation was analyzed by dividing the provinces of China in four economic regions, namely the east, center, west and North East region. The results from the analysis revealed a significant, but weak positive relation between FDI and sulphur dioxide, however, rejected the association of water pollutant emission with same. On the aggregate level as well, panel data analysis throws similar relation of all provinces in the analysis. Lastly, in case of cross region analysis, the eastern region has been encountered as contributing towards water emission only, where center, northeast and west region as contributing towards both water waste and sulphur mission. This study suggests that uniform environmental regulation in all the regions, focusing on foreign firms which use latest technology to reduce both the emission of air and water pollution and strengthening the legal system and market mechanism of property rights protection can be helpful to reduce and control environmental problems in China.